Tourism and Public Policy - Lemos Baptista, João Manuel; Pocinho, Margarida; Nechita, Florin (Universitatea Transilvania Brasov, 2019)
This paper addresses the connection between tourism and public policies from a descriptive and secondary data analysis perspective, aiming to contribute to a deeper reflection on issues of tourism in terms of concepts and statement of policies that should be adopted in various tourist areas. This article intends to deepen the various concepts of tourism and to address the public policies that should be adopted in tourist regions or countries, referring to the importance of public policies in the territories that have their main economic and social activity in the tourism sector. The reference to tourism as a development factor is based on evidence for the effectiveness of the sector for job creation and enormous potential for the recovery of disadvantaged areas. Some considerations about tourism policies in Portugal are presented.
Keywords: tourism; SOCIAL SCIENCES::Social sciences::Political science::Peace and development research; public policy